2012
DOI: 10.1111/anec.12011
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fragmented QRS Complex with Myocardial Reperfusion in Acute ST‐Elevated Myocardial Infarction

Abstract: In this study, we aimed to evaluate the relationship between TIMI myocardial perfusion (TMP) grade, as an indicator of myocardial reperfusion, and fragmented QRS (fQRS) in standard 12-lead electrocardiogram. Also, we evaluate fQRS is an additional indicator of myocardial reperfusion. One hundred patients admitted with first STEMI to Coronary Intensive Care Unit and who were used thrombolytic therapy was included in this retrospective study. Standard 12-lead electrocardiogram records of patients simultaneous wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Similar findings have been determined in the study by Angue et al, in which the presence of fragmented QRS in patients with acute myocardial infarction was found to be associated with significant decrease in EF [18]. Also, the study by Erdem et al, performed on patients with acute ST elevation myocardial infarction, found a significant negative correlation between fragmented QRS and left ventricular ejection fraction, which supports our findings [19]. While the non-fragmented group’s mean EF was 49.93±10.48 (%), the mean EF in patients with ≥4 fragmentations was 38.54±11.84 (%).…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been determined in the study by Angue et al, in which the presence of fragmented QRS in patients with acute myocardial infarction was found to be associated with significant decrease in EF [18]. Also, the study by Erdem et al, performed on patients with acute ST elevation myocardial infarction, found a significant negative correlation between fragmented QRS and left ventricular ejection fraction, which supports our findings [19]. While the non-fragmented group’s mean EF was 49.93±10.48 (%), the mean EF in patients with ≥4 fragmentations was 38.54±11.84 (%).…”
Section: Discussionsupporting
confidence: 93%
“…The degrees of myocardial ischemia and myocardial scars were correlated with the poor prognosis of patients [ 28 ]. However, previous studies [ 29 31 ] reported that the occurrence of myocardial coronary perfusion abnormality in fQRS patients is significantly enhanced, and the predictive value for the cardiac death is significantly higher compared to non-fQRS patients. A previous study [ 32 ] reported that the fQRS complex acts as a prognostic marker for microvascular reperfusion and LV dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…And one study was excluded because the researchers assessed the correlation between fQRS and left ventricular aneurysm instead of myocardial scar [8]. Eight studies (2560 patients) were finally included in the systematic review [5,[9][10][11][12][13][14][15]. Table 1 shows the characteristics of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight related studies the reported sensitivity varied in a wide range: 32% [11] to 86% [5]. Two studies reported a sensitivity below 50% for fQRS [11,14], and the sensitivity of fQRS in another six studies was higher than 60%. In the research by Wang et al [11] the patients' ECGs were performed within three months of the myocardial perfusion imaging (MPI) studies (not at the same time as the MPI).…”
Section: Fragmented Qrs Vs F-w-qrs Complexesmentioning
confidence: 99%
See 1 more Smart Citation